Vancomycin-Resistant Enterococci (VRE) in Nigeria: The First Systematic Review and Meta-Analysis - Yusuf Wada; Azian Binti Harun; Chan Yean Yean; Abdul Rahman Zaidah (MDPI AG, 2020)
Vancomycin-Resistant Enterococci (VRE) are on the rise worldwide. Here, we report the first prevalence of VRE in Nigeria using systematic review and meta-analysis. International databases MedLib, PubMed, International Scientific Indexing (ISI), Web of Science, Scopus, Google Scholar, and African journals online (AJOL) were searched. Information was extracted by two independent reviewers, and results were reviewed by the third. Two reviewers independently assessed the study quality using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist. OpenMeta analyst was used. The random effect was used, and publication bias was assessed using a funnel plot. Between-study heterogeneity was assessed, and the sources were analysed using the leave-one-out meta-analysis, subgroup analysis, and meta-regression. Nineteen studies met the eligibility criteria and were added to the final meta-analysis, and the study period was from 2009-2018. Of the 2552 isolates tested, 349 were VRE, and E. faecalis was reported the most. The pooled prevalence of VRE in Nigeria was estimated at 25.3% (95% CI; 19.8-30.8%; I2 = 96.26%; p < 0.001). Between-study variability was high (t2 = 0.011; heterogeneity I2 = 96.26% with heterogeneity chi-square (Q) = 480.667, degrees of freedom (df) = 18, and p = 0.001). The funnel plot showed no publication bias, and the leave-one-out forest plot did not affect the pooled prevalence. The South-East region had a moderate heterogeneity though not significant (I2 = 51.15%, p = 0.129). Meta-regression showed that all the variables listed contributed to the heterogeneity except for the animal isolate source (p = 0.188) and studies that were done in 2013 (p = 0.219). Adherence to proper and accurate antimicrobial usage, comprehensive testing, and continuous surveillance of VRE are required.